Photography and literature in the twentieth century - Cunningham, David (Lecturer in English Literature); Fisher, Andrew; Mays, Sas (Cambridge Scholars, 2005)
Photography and Literature in the Twentieth-Century offers an accessible and fresh approach to an object of interdisciplinary research that is currently receiving increased international attention. Providing a broad historical schema, and examining pivotal moments within it, the collection brings together a range of writers and practitioners who help to guide the reader through a historical cross-section of current work in this area. Unlike most existing studies, this volume considers both ke ...